Immunohistochemical correlation of mast cells and angiogenesis in oral lichen planus. (October 2022) - Girdhar, Akhil; Kamboj, Mala; Narwal, Anjali; Devi, Anju; Anand, Rahul; Gupta, Ambika
Abstract: Objective: The study was conceived with an aim to correlate mast cell expression and angiogenesis in oral lichen planus (OLP) and inflamed oral mucosa. Design: An observational study was performed on fifty tissue blocks of OLP and inflamed oral mucosa which were stained immunohistochemically using mast cell tryptase, CD34 and CD105. The data was analysed using Mann Whitney U-test and Spearman's rank correlation coefficient test (p < 0.05). Results: OLP showed significantly higher mast cell density for total and degranulated mast cells and higher microvessel density (CD105) compared to inflamed oral mucosa (p = 0.006, 0.000). Microvessel density, total and mean vascular area (CD34) were higher in inflamed oral mucosa with a non significant difference (p = 0.985, 0.977, 0.720). Mild negative association was observed between mast cells and angiogenesis in OLP (p = 0.879). A significant positive correlation was seen between degranulated mast cells and microvessel density (CD34) in inflamed oral mucosa (p = 0.009). Conclusion: Mast cells execute different roles in OLP depending upon stage of the disease. We found that although degranulation of mast cells is not the predominant pathway for angiogenesis in OLP, yet is one of the important precursor phenomena in inflamed tissues. Highlights: Mast cells are involved in the pathogenesis of oral lichen planus. Increased angiogenesis is associated with increased malignant risk potential in OLP. Mast cells and angiogenesis are increased in chronic inflammatory disorders.